2017
DOI: 10.1902/jop.2017.160678
|View full text |Cite
|
Sign up to set email alerts
|

A Clinical Validation of Self‐Reported Periodontitis Among Participants in the Black Women’s Health Study

Abstract: Background There is a paucity of data on the validity of self-report of periodontal disease in African Americans. The Black Women’s Health Study (BWHS), a United States national cohort study of 59,000 black women followed via mailed questionnaires since 1995, offered the opportunity to clinically validate self-reported periodontitis among a sample of participants. Methods Oral health questionnaires were sent to study participants residing in Massachusetts. Respondents living in the Boston metro area were inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
47
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 38 publications
(58 citation statements)
references
References 22 publications
9
47
0
2
Order By: Relevance
“…The hypothesis was validated, as all examined self‐reported periodontal screening questions, demographic characteristics such as age and gender, tobacco use, and a number of systemic medical conditions were significantly associated with moderate and severe bone loss. Each individual variable demonstrated generally better predictive ability for severe bone loss compared with moderate bone loss which is in agreement with a previous report . Therefore, this study supports the potential use of these variables in a subjective screening tool for periodontal disease.…”
Section: Discussionsupporting
confidence: 92%
“…The hypothesis was validated, as all examined self‐reported periodontal screening questions, demographic characteristics such as age and gender, tobacco use, and a number of systemic medical conditions were significantly associated with moderate and severe bone loss. Each individual variable demonstrated generally better predictive ability for severe bone loss compared with moderate bone loss which is in agreement with a previous report . Therefore, this study supports the potential use of these variables in a subjective screening tool for periodontal disease.…”
Section: Discussionsupporting
confidence: 92%
“…To our knowledge, this is the largest analysis of self‐reported oral health conducted exclusively in a sample of African American women. Oral health status was assessed at one point in time using previously validated self‐report measures, some of which were validated clinically in a subset of the BWHS population . We found that the predictors of self‐reported oral health in the BWHS are largely consistent with what has been observed in other populations, but we also found different risk factor patterns according to the outcome studied.…”
Section: Discussionsupporting
confidence: 74%
“…Periodontitis in the NHANES was measured by a dental professional using the CDC case definition . As described above, our validation of self‐reported periodontal disease demonstrated comparable validity . It is possible that in the BWHS, being older and less educated resulted in fewer dental visits and thus fewer opportunities to be diagnosed with periodontal disease.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations